A new species of Cordia (Cordiaceae) for the state of Minas Gerais, Brazil - Guimaraes, Elsie Franklin; Ranga, Neusa Taroda [UNESP]; Miranda de Melo, Jose Iranildo (Consejo Superior Investigaciones Cientificas-csic, 2016)
A new species of the genus Cordia (Cordiaceae), C. kuhlmannii E.F. Guim., N.T. Ranga & J.I.M. Melo, for the state of Minas Gerais, Brazil is described and illustrated. The species, belonging to the section Gerascanthus is characterized mainly by irregular calyx lobes, corolla with narrow tube, stamens with glabrate bases and long branches of the style.
Keywords: Boraginales; Cordiaceae; Gerascanthus; South America; taxonomy